2018
DOI: 10.1002/esp.4540
|View full text |Cite
|
Sign up to set email alerts
|

Understanding fracture distribution and its relation to knickpoint evolution in the Rio Icacos watershed (Luquillo Critical Zone Observatory, Puerto Rico) using landscape‐scale hydrogeophysics

Abstract: The Rio Icacos watershed in the Luquillo Mountains (Puerto Rico) is unique due to its extremely rapid weathering rates. The watershed is incised into a quartz diorite that has developed a large knickzone defining the river profile. Regolith thickness within the watershed generally decreases from 20 to 30 m at the ridges to several meters in the quartz diorite‐dominated valley to tens of centimeters near the major river knickpoint, as determined from previous studies. Above the knickzone, we observe spheroidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Buss et al (2013) states that, "Both borehole profiles indicate that the weathering zone extends to well below the stream channel in this upland catchment; hence weathering depth is not controlled by the stream level within the catchment and not all of the water in the watershed is discharged to the stream." In a recent study at the Luquillo CZO, but at a catchment overlaying quartz diorite bedrock, Comas, Wright, Hynek, Fletcher, and Brantley (2019), using geophysical imaging and modeling, also finds bedrock fractures at tens-of-meter below the valley floor, except at knickpoints of stream incision. Deep fracturing and weathering under a humid tropical climate may be the norm, and thus bedrock weathering, and its capacity as long-term CO 2 sink, may be best constrained by accounting for both river and groundwater export of the weathering products.…”
Section: Groundwater Exportingmentioning
confidence: 96%
“…Buss et al (2013) states that, "Both borehole profiles indicate that the weathering zone extends to well below the stream channel in this upland catchment; hence weathering depth is not controlled by the stream level within the catchment and not all of the water in the watershed is discharged to the stream." In a recent study at the Luquillo CZO, but at a catchment overlaying quartz diorite bedrock, Comas, Wright, Hynek, Fletcher, and Brantley (2019), using geophysical imaging and modeling, also finds bedrock fractures at tens-of-meter below the valley floor, except at knickpoints of stream incision. Deep fracturing and weathering under a humid tropical climate may be the norm, and thus bedrock weathering, and its capacity as long-term CO 2 sink, may be best constrained by accounting for both river and groundwater export of the weathering products.…”
Section: Groundwater Exportingmentioning
confidence: 96%
“…Ground penetrating radar (GPR) surveys indicated that eroding channels in the hillside leading to the river are usually co-located with vertical zones of enhanced GPR reflection. These were interpreted as deep fracture zones filled with rindletted corestones (Comas et al, 2019). Field measurements across these fracture zones showed coincident decreases in terrain conductivity and increases in magnetic susceptibility (Comas et al, 2019).…”
Section: How Subsurface Particle Transport Occurs At Río Icacosmentioning
confidence: 94%
“…These were interpreted as deep fracture zones filled with rindletted corestones (Comas et al, 2019). Field measurements across these fracture zones showed coincident decreases in terrain conductivity and increases in magnetic susceptibility (Comas et al, 2019). To test what might cause this, we conducted magnetic susceptibility (MS) measurements in the laboratory and observed that the MS values decreased from corestones ≈ rindlets > seep sediments > soils (Table S-1).…”
Section: How Subsurface Particle Transport Occurs At Río Icacosmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they may not be spatially representative of subsurface weathering at a site. Near‐surface geophysics can augment data from cores, penetrating through the weathering profile in surveys spanning 10 1 –10 3 ‐m horizontal scales (Comas et al, 2019; Parsekian et al, 2015). For example, hillslope‐scale seismic refraction surveys can be used to compute seismic velocity tomograms, which represent horizontal and vertical variations in weathering (e.g., Befus et al, 2011).…”
Section: Introductionmentioning
confidence: 99%